Dimensi Teologi dalam Ritual Sedekah Bumi Masyarakat Made - Hassan Nugroho (Islamika Inside: Jurnal Keislaman dan Humaniora, 2018)
This study discusses the phenomenon of tradisi sedekah bumi (giving alms to the mother Earth) in the Village of Made, Sambikerep, Surabaya. The tradition of giving alms to the mother Earth --which has been commonly performed by agrarian society (rural people) in Java as a manifestation of thankfulness upon "the Unseen Power" who is regarded as having power to determine successfulness and failure of harvest-- has been, in fact, well preserved by the people of Made until the present days. It has been obviously known that the people of Made are no longer an agrarian society; rather they have become a part of a modern urban society of Surabaya. In other words, theological values of tradisi sedekah bumi performed by the people of Made are intended to be compatible with the development of modern social reality. The study, therefore, seeks to scrutinize the practice of tradisi sedekah bumi performed by the people of Made along with its theological dimensions. It is found that the tradition has been passed on generation to generation as a manifestation of gratefulness, an appreciation to the Earth, a means of strengthening brotherhood among the plural community, and a way to gain prosperity and blessing from God.